The Level of Academic Flow Among 11th Grade Students at State Islamic Senior High School 2 Hulu Sungai Utara - Muhammad Syafi'i; Musfichin; Siti Faridah (Interdisciplinary Journal of Social Science and Education (IJSSE), 2024)
Academic Flow is a state in which an individual is fully focused and engaged in academic work or activities. It occurs when someone enjoys their work and maintains a high level of concentration, especially if the task aligns with their interests. The level of academic flow reflects the extent to which an individual experiences a flow state during the learning process or participation in academic activities. This flow experience encompasses full concentration, excitement, and a loss of awareness of time. The aim of this research is to assess the level of academic flow among students in the 11th grade of State Islamic Senior High School 2 Hulu Sungai Utara. The method employed is a quantitative survey with random sampling, involving 176 students. Data were collected through a questionnaire survey. The results indicate that the majority of students (60.8%) experience a moderate level of academic flow, 39.2% have a high level, while no students exhibit a low level (0%).